Molecular Epidemiology of Antimicrobial Resistance of Uropathogenic Escherichia coli Isolates from Patients with Urinary Tract Infections in a Tertiary Teaching Hospital in Iran - Neamati, Foroogh; Khorshidi, Ahmad; Moniri, Rezvan; Hosseini Tafreshi, Seyed Ali (Microbial drug resistance (Larchmont, N.Y.), 2020)
To characterize the resistance patterns of uropathogenic (UPEC) in a Tertiary Teaching Hospital in Iran, we conducted a descriptive epidemiology study using molecular techniques. The subjects consisted of patients having acute urinary tract infection, who were enrolled in the study from 2014 to 2017. The antimicrobial susceptibility profile of 101 UPEC isolates was determined by Kirby-Bauer disc diffusion method. Extended spectrum β-lactamase (ESBL) was detected by the double-disk synergy test. Biofilm formation was done using microtiter plates. The presence of virulence genes ( , , , , , , , and ) was evaluated by a PCR. Molecular typing of UPEC isolates was performed with and multilocus sequence typing (MLST). 70.3% of isolates were multidrug-resistant. 37.6% of isolates were Extended spectrum β-lactamases (ESBLs) producer. Strong biofilm formation was seen in 27.7%. Forty-seven different allelic variants were identified. Among identified allelic variants, the most common types were f1 (18.8%) and f14 (18.8%). ST131 (54.5%) was the most prevalent clonal group significantly correlated with the gene. Seven sequence types (STs) were detected only once (ST405, ST410, ST450, ST636, ST648, ST1193, and ST6451). Clonal groups showed no significant differences in terms of antibiotic resistance patterns. There was no significant difference between virulence genes and antibiotic resistance patterns in the studied clonal groups. To our knowledge, the present study is the first study in Iran that investigated the genotypic diversity of UPEC isolates by MLST and typing methods. The two methods might serve as a useful molecular test for surveillance and epidemiological studies of isolates.